2017
DOI: 10.4041/kjod.2017.47.4.256
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of changes in the transverse dental axis between patients with skeletal Class III malocclusion and facial asymmetry treated by orthognathic surgery with and without presurgical orthodontic treatment

Abstract: ObjectiveTo evaluate transverse skeletal and dental changes, including those in the buccolingual dental axis, between patients with skeletal Class III malocclusion and facial asymmetry after bilateral intraoral vertical ramus osteotomy with and without presurgical orthodontic treatment.MethodsThis retrospective study included 29 patients with skeletal Class III malocclusion and facial asymmetry including menton deviation > 4 mm from the midsagittal plane. To evaluate changes in transverse skeletal and dental v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
(25 reference statements)
1
11
0
1
Order By: Relevance
“…The vertical mandibular molar movement with the slight extrusion observed in our study occurred because of dental decompensation of the mandibular posterior teeth, simultaneously to the clockwise rotation of the mandible observed in these patients. The present study findings are in agreement with the study by Song et al 37 Importantly, the morphology, both size and shape, 8 of the mandibular symphysis serves as a primary reference for facial profile esthetics and determines the planning of the position of the mandibular incisors during orthognathic surgery. During orthodontic treatment, limiting the movement of the incisor within the trabecular bone structure is essential for obtaining better results, stability, and periodontal health.…”
Section: Discussionsupporting
confidence: 93%
“…The vertical mandibular molar movement with the slight extrusion observed in our study occurred because of dental decompensation of the mandibular posterior teeth, simultaneously to the clockwise rotation of the mandible observed in these patients. The present study findings are in agreement with the study by Song et al 37 Importantly, the morphology, both size and shape, 8 of the mandibular symphysis serves as a primary reference for facial profile esthetics and determines the planning of the position of the mandibular incisors during orthognathic surgery. During orthodontic treatment, limiting the movement of the incisor within the trabecular bone structure is essential for obtaining better results, stability, and periodontal health.…”
Section: Discussionsupporting
confidence: 93%
“…Stable occlusal contacts can make the postoperative outcome more predictable. Since occlusal settling through post-surgical orthodontic treatment allows eliminating the posterior occlusal interferences, the mandible rotated counterclockwise, providing vertical and horizontal movement to compare to the immediate postoperative position [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, conduction of randomized clinical trials for the comparison of the two approaches is difficult due to the existing ethical concerns. Song et al, and Byugiu et al reported similar rate of relapse by direct measurement between the two groups [3,[24][25][26][27][28]. Xiatong et al [29] and Wang et al [26] reported similar rate of relapse between the two groups by measuring the magnitude of condylar displacement and condylar remodeling after surgery, respectively.…”
Section: Treatment Timementioning
confidence: 99%
“…In terms of type of surgery, 484 patients had undergone bimaxillary surgery and 171 had undergone mandibular surgery alone. Also, 29 patients had undergone bilateral vertical subcondylar osteotomy for mandibular setback and correction of asymmetry [ 28 ] Of all patients, 86 had undergone extraction of maxillary premolars [ 23 - 25 ]. The amount of relapse of the maxilla and mandible was calculated by comparing the position of the maxilla and mandible immediately after surgery and at the time of debonding in all studies, except for one study that evaluated relapse during a 20-month period [ 10 ].…”
Section: Introductionmentioning
confidence: 99%